Precision Medicine for Acute Myeloid Leukemia - Lai, Catherine (Expert Rev Hematol, 2015)
The goal of precision medicine is to personalize therapy based on individual patient variation, to correctly select the right treatment, for the right patient, at the right time. Acute myeloid leukemia (AML) is a heterogeneous collection of myeloid malignancies with diverse genetic etiology and the potential for intra-patient clonal evolution over time. We discuss here how the precision medicine paradigm might be applied to the care of AML patients by focusing on the potential roles of targeting therapy by patient-specific somatic mutations and aberrant pathways, ex-vivo drug sensitivity and resistance testing, high sensitivity measurements of residual disease burden and biology along with potential clinical trial and regulatory constraints.